Comparative Evaluation of Antibacterial Efficacy of Commercially Available Rhamnosus Derived Therapeutic Agent Against Cariogenic Microorganism (Asian Journal of Pharmaceutics (AJP), 2025)
This study was designed to evaluate and compare the effectiveness of probiotics, synbiotics, and CHX0.2%-against the Streptococcus mutans and Streptococcus salivarius, which are considered the most importanttargets in the pathways of causation that lead to dentistry-carious lesions. Materials and Methods: Pure culturesof S. mutans ATCC 25175 and S. salivarius ATCC 25975 were grown on Muller-Hinton agar and tested at 10⁶CFU/mL bacterial inoculum. Assessing anti-bacterial properties was done through the assessment of the zone ofinhibition (ZOI). Tooth surface swabs samples were evaluated on Mutans Sanguis Agar, with confluent coloniescounted after 24-48 hours for biofilm assessment. Results: The highest ZOI produced by the CHX 0.2% was forS. mutans (25 ± 1.8 mm) followed by probiotics (18 ± 1 mm) and synbiotics (12 ± 0 mm). S. salivarius showedcorresponding values of ZOI 24.3 ± 2.1 mm for CHX 0.2% and 16.6 ± 1.2 mm for probiotics and 13 ± 1 mmfor synbiotics. One-way ANOVA explained that there is a statistically significant difference among groups (p